THE POTTERY ANT HOUSEWARE OF THE VOLNA 12 SETTLEMENT FROM EXCAVATIONS 2013-2015 - Kladcenko, Ol'ga Vital'evna (History, Archeology and Ethnography of the Caucasus, 2021)
The settlement of Volna 12 was excavated in 2013– 2015, on the Taman Peninsula. The settlement is located on the south-western coast of the Taman Peninsula, 5.8 km north-west of the outskirts of the Volna village and 1.8 km north of Cape Panagia. The period of the settlement's existence falls on the late 17th (possibly the beginning of the 18th) – early 19th centuries. The settlement with an area of ​​31 hectares has been fully explored, so we have the opportunity to work with its materials in full. The previously unpublished ceramic material of the settlement - dishes and ceramic household items – is considered in the article by groups and categories. Particular attention is paid to non-glazed ceramics, which for a long time remained outside the interests of researchers. The article considers such categories of ceramic vessels as Aquarius, jugs, bowls, household vessels, braziers. The settlement did not exist for a very long period of time (about 100– 150 years), therefore, chronological differences in the ceramic material cannot be found. Obviously, it mainly comes from one or several centres of the South-Eastern Crimea, but the question of the centre of production of these vessels remains unresolved.
Keywords: archeology of modern times; ceramics; Crimea; Taman